Bone and TNF in rheumatoid arthritis: clinical implications - Manara, Maria (RMD Open, 2015)
Experimental data have demonstrated that tumour necrosis factor (TNF) plays a significant role in systemic and local bone loss related to rheumatoid arthritis (RA). In clinical studies on patients with RA, treatment with TNF inhibitors was able to arrest systemic bone loss assessed by bone mineral density and bone turnover markers, but there is scarce evidence of a clinically meaningful effect of TNF inhibition in preventing fractures. TNF inhibitors showed a higher efficacy in reducing radiographic progression related to the disease compared to methotrexate in randomised clinical trials. Data from observational studies seem to confirm the effectiveness of anti-TNF therapy in reducing joint damage evolution.